2020
DOI: 10.3390/nu12041080
|View full text |Cite
|
Sign up to set email alerts
|

Association between Self-Reported Eating Rate, Energy Intake, and Cardiovascular Risk Factors in a Multi-Ethnic Asian Population

Abstract: Eating faster is associated with greater body mass index (BMI), but less is known about the relationships between eating rate, energy intake, body composition, and cardio-metabolic risk factors in different Asian ethnic groups. Using data from the Singapore Multi-Ethnic Cohort (n = 7011; 21–75 y), we investigated associations between self-reported eating rate (SRER), with energy intake, body composition, blood pressure, and blood lipids. SRER and lifestyle was assessed using interviewer-administered questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 52 publications
1
31
0
Order By: Relevance
“…Self-reported eating rate (SRER) was recorded by each individual based on a previously published approach [3,21], and previous research has shown that SRER estimates do reflect experimentally observed eating rates at a group level [22,23]. Each participant self-assessed their eating rate in response to the question: "How fast is your rate of eating?…”
Section: Assessment Of Self-reported Eating Rate (Srer) Diet and Bodmentioning
confidence: 99%
See 2 more Smart Citations
“…Self-reported eating rate (SRER) was recorded by each individual based on a previously published approach [3,21], and previous research has shown that SRER estimates do reflect experimentally observed eating rates at a group level [22,23]. Each participant self-assessed their eating rate in response to the question: "How fast is your rate of eating?…”
Section: Assessment Of Self-reported Eating Rate (Srer) Diet and Bodmentioning
confidence: 99%
“…Details on assessment procedures for body composition have been reported in our previous paper [3]. In brief, body weight, height, and waist-circumference (WC) were assessed according to WHO standards and were taken to the nearest 0.1 kg, 0.1 m, or 0.1 cm, respectively, by trained personnel.…”
Section: Assessment Of Self-reported Eating Rate (Srer) Diet and Bodmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, no studies have been conducted in Swedish or Greek populations. The epidemiological self-reported literature on eating rate is also location specific, as it has previously included predominantly Japanese populations (for example 18-year-old women [ 27 ], 29- to 39-month-old children [ 28 ] and middle-aged men and women [ 29 ]), as well as middle-aged women in New Zealand [ 30 ], Dutch adults [ 24 ], Singaporean adults [ 31 ] and South Korean adults [ 32 ]. Thus, data across additional regions and target populations are also needed to clarify the generalizability of past findings.…”
Section: Introductionmentioning
confidence: 99%
“…This is a population-based cohort study of Singapore citizens and permanent residents aged 21-75 years, mainly comprising three major ethnic groups in Singapore (Chinese, Malay, and Indian). Detailed information is available http://blog.nus.edu.sg/sphs/the-first-sphs-follow-up/, accessed on 5 November 2020 and a previous publication Teo et al [31]. Data collection for the follow-up consisted of two parts: (1) a home interview and (2) a physical examination at a health screening center.…”
Section: Study Population and Data Collectionmentioning
confidence: 99%